Improving Students’ Vocabulary Mastery through Visual Learning Style - Eka Karina Nadhifah Putri; Aminah Aminah; Andi Patmasari; Mochtar Marhum (Hasanuddin University, 2025)
The aim of this research is to find whether the use of visual learning style can improve students' vocabulary of the seventh grade of MTsN 2 Kota Palu. This research used a quantitative research design, using a pre-experimental design, this type of research design only has one class, namely the experimental class. that means only one group of students are given a pretest, treatment and posttest. The population of this study was 7th grade students at MTsN 2 Palu City, totaling 256 students, using purposive sampling, 32 students in class VII D were selected. Data collection in this study used tests in the form of pretests and posttests. The results of this study showed that visual learning styles can improve students' vocabulary mastery, as evidenced by an increased in the average score from 14.06 (pretest) to 72.40 (posttest), with an increase of 58.34. These findings indicated that the visual learning style strategy is effective in improving students' vocabulary mastery.